2022
DOI: 10.1111/risa.14080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air pollution and weather on the initial COVID‐19 outbreaks in United States, Italy, Spain, and China: A comparative study

Abstract: Contrasting effects have been identified in association of weather (temperature and humidity) and pollutant gases with COVID‐19 infection, which could be derived from the influence of lockdowns and season change. The influence of pollutant gases and climate during the initial phases of the pandemic, before the closures and the change of season in the northern hemisphere, is unknown. Here, we used a spatial‐temporal Bayesian zero‐inflated‐Poisson model to test for short‐term associations of weather and pollutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
1
1
0
Order By: Relevance
“…Our findings indicate that some weather variables affected the total positive tests across Teesside in 2020. We found positive tests were reduced by higher temperatures, in accordance with previous research (Ganslmeier et al, 2021; Alaniz et al, 2023; Nottmeyer et al, 2023). This is probably due to both indirect and direct mechanisms, as warmer weather encourages outdoor (rather than indoor) socialising and increased indoor ventilation, while also reducing transmissibility of the virus particles (Ganslmeier et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings indicate that some weather variables affected the total positive tests across Teesside in 2020. We found positive tests were reduced by higher temperatures, in accordance with previous research (Ganslmeier et al, 2021; Alaniz et al, 2023; Nottmeyer et al, 2023). This is probably due to both indirect and direct mechanisms, as warmer weather encourages outdoor (rather than indoor) socialising and increased indoor ventilation, while also reducing transmissibility of the virus particles (Ganslmeier et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…The relationship between COVID-19 infection and weather is also complex. Higher temperatures have been associated with a reduction in cases in many countries including the UK (Ganslmeier et al, 2021;Alaniz et al, 2023;Nottmeyer et al, 2023), though a minority of studies have reported a positive effect (Tan & Schultz, 2022). Increased rainfall effects are more uncertain due to less research focus, with a metaanalysis finding evidence of increased infections (Tan & Schultz, 2022), while other research detected no relationship (Ganslmeier et al, 2021).…”
Section: Introductionmentioning
confidence: 99%